2015
DOI: 10.7150/ijbs.12296
|View full text |Cite
|
Sign up to set email alerts
|

Triterpenoid Saponin W3 from Anemone flaccida Suppresses Osteoclast Differentiation through Inhibiting Activation of MAPKs and NF-κB Pathways

Abstract: Excessive bone resorption by osteoclasts within inflamed joints is the most specific hallmark of rheumatoid arthritis. A. flaccida has long been used for the treatment of arthritis in folk medicine of China; however, the active ingredients responsible for the anti-arthritis effects of A. flaccida are still elusive. In this study, W3, a saponin isolated from the extract of A. flaccida was identified as the major active ingredient by using an osteoclast formation model induced by receptor activator of nuclear fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 28 publications
3
21
0
Order By: Relevance
“…Osteoclasts are derived from osteoclast precursor cells (OPCs), which originate from the monocyte/macrophage lineage. Previous studies have demonstrated that the osteoblast-associated synthesis and secretion of receptor activator of nuclear factor κB ligand (RANKL) and osteoclast-associated RANK are essential in osteoclastogenesis, and that RANK on monocytes binds to RANKL, initiating osteoclast differentiation ( 4 , 5 ). Furthermore, macrophage-derived proinflammatory mediators in RA directly contribute to the degradation of articular cartilage and subchondral bone, and the activation of RA monocytes/macrophages occurs locally and in the peripheral circulation ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Osteoclasts are derived from osteoclast precursor cells (OPCs), which originate from the monocyte/macrophage lineage. Previous studies have demonstrated that the osteoblast-associated synthesis and secretion of receptor activator of nuclear factor κB ligand (RANKL) and osteoclast-associated RANK are essential in osteoclastogenesis, and that RANK on monocytes binds to RANKL, initiating osteoclast differentiation ( 4 , 5 ). Furthermore, macrophage-derived proinflammatory mediators in RA directly contribute to the degradation of articular cartilage and subchondral bone, and the activation of RA monocytes/macrophages occurs locally and in the peripheral circulation ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has confirmed that osteoblast-associated synthesis and secretion of receptor activator of nuclear factor κB ligand (RANKL) and osteoclast-associated RANK are essential in osteoclastogenesis and that RANK binds to RANKL on monocytes, initiating differentiation of osteoclasts [17][18][19]. During this process, an essential transcription factor, nuclear factor kappa B (NF-κB), is activated by the binding of RANKL and RANK via Tumor Necrosis Factor Receptor-associated Factor 6 (TRAF6) and then transported into the nucleus, where it combines with c-Fos, another transcription factor, to activate nuclear factor of activated T-cells, cytoplasmic 1 (NFATc1) to induce osteoclastogenesis [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Receptor activator of nuclear factor κB ligand (RANKL) is a key factor for osteoclasts formation and differentiation. Celastrol, curcumol, pristimerin, andrographolide, jolkinolide B, triterpenoid saponin W3, icariin, aconine, boldine, curcumin, and triptolide can inhibit RANKL‐induced osteoclastogenesis (Gan et al, ; Kong et al, ; Liu et al, ; Ma et al, ; Nanjundaiah et al, ; Shang et al, ; Tong et al, ; Wei, Ping, You, Qiang, & Tao, ; Yu et al, ; Zeng et al, ; Zhai et al, ; Zhao et al, ). Cathepsin K, an enzyme expressed by osteoclasts, degrades key components of bone and cartilage in RA, whose level is directly up‐regulated by RANKL during osteoclastogenesis (Sun et al, ).…”
Section: The Anti‐ra Activities Of Chemical Constituents From Herbal mentioning
confidence: 99%